Relative importance of attribute preferences for radial vs. femoral arterial access: A crowdsourcing study of healthy online‐recruited volunteers. Issue 7 (20th October 2018) - Ross, Jason; Vidovich, Mladen I.
Abstract: Introduction: Percutaneous coronary intervention (PCI) is typically performed with vascular access provided by the radial or femoral artery. However, little is known about how patients value aspects of these different vascular access approaches. Methods : Conjoint analysis is a survey‐based statistical technique used in market research that helps determine how individuals value different attributes that make up a particular product or services. We utilized conjoint analysis to assess the relative importance of four attributes associated with PCI: access site, risk of bleeding, hospital stay, and radiation exposure. Participants were healthy individuals recruited by Amazon Mechanical Turk (MTURK). After completing a conjoint analysis survey, the software Conjoint.ly was used to calculate the relative importance for these four different attributes of PCI. Results : The relative importance of hospital stay, radiation exposure, bleeding risk, and procedure site was 32.7% (95% CI 29.5–35.8), 27.3% (95% CI 24.8–29.8), 24.4% (95% CI 22.3–26.5), and 15.7% (95% CI 13.6–17.8), respectively. The difference between these groups was statistically significant ( P ‐value < 0.00001). The difference between duration of hospital stay and radiation exposure was statistically significant ( P ‐value < 0.00433). Conclusion : Patients undergoing PCI place largest relative value on duration of hospital stay. Access site appears the least valued attribute. These findings carry implications to guide further research on access site choices and the consent process in the context of shared decision‐making.